Design Elements and Users Perceptual Response: A Case of Window Display Design for Adolescent Merchandising - Kanokwan Somoon; Nopadon Sahachaisaree (My University, 2012)
Abstract Window displays, as a part of selling strategies, not only convey the type and positioning of mechanize, but also the promotional strategies and corporate images. The study uses window displays for clothing to examine patterns, selling strategies, merchandize types, and target groups. It investigates the effects of design elements on the customers perceptual responding to configurations. The theoretical framework bases on marketing concepts, visual perception principles, Gestalt psychology, and design's principle and elements. Research found that 14 factors in the design affected to perception. The study perception indicates that purchasing desire and attraction had more relation.
Keywords: Design Education and Practice